2020
DOI: 10.14202/vetworld.2020.1605-1612
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Channa striata extract and standard eradication regimen on asymmetric dimethylarginine in Helicobacter pylori gastritis rat model

Abstract: Background and Aim: The presence of gastric mucosa or submucosa inflammation due to Helicobacter pylori leads to histological changes. Gastric injury, pro-inflammatory factors, and oxidative stress in H. pylori infection produce asymmetric dimethylarginine (ADMA), which are a competitive inhibitor of nitric oxide synthase. Investigations were carried out aimed at finding new drugs derived from natural products for the treatment of H. pylori. Channa striata is known to have in vitro anti-inflammatory and antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Snakehead fish extract supplementation was described as a useful method to eradicate H. pylori in rats, although its superiority when compared to standard first-line antibiotic treatment needs to be confirmed by further studies [ 97 ]. By contrast, the effect of the extracts from the Channa striata fish on an H. pylori -induced gastritis rat model was controversial since it worsened the severity of gastritis when administrated alone, but seemed to contribute to the improvement of the disease when combined with the standard triple therapy [ 98 ]. Another study conducted in mice reported that after six weeks of supplementation with astaxanthin from shrimp cephalothorax, H. pylori -infected mice showed an increase in splenocytes synthesis of interferon-gamma, IL-2, and IL-10, although the biological meaning of the changes in the cytokine release pattern remains to be explained [ 99 ].…”
Section: Management Of Helicobacter Pylori Infectionmentioning
confidence: 99%
“…Snakehead fish extract supplementation was described as a useful method to eradicate H. pylori in rats, although its superiority when compared to standard first-line antibiotic treatment needs to be confirmed by further studies [ 97 ]. By contrast, the effect of the extracts from the Channa striata fish on an H. pylori -induced gastritis rat model was controversial since it worsened the severity of gastritis when administrated alone, but seemed to contribute to the improvement of the disease when combined with the standard triple therapy [ 98 ]. Another study conducted in mice reported that after six weeks of supplementation with astaxanthin from shrimp cephalothorax, H. pylori -infected mice showed an increase in splenocytes synthesis of interferon-gamma, IL-2, and IL-10, although the biological meaning of the changes in the cytokine release pattern remains to be explained [ 99 ].…”
Section: Management Of Helicobacter Pylori Infectionmentioning
confidence: 99%
“…Gastric injury or infection induces inflammation of the gastric mucosa. Helicobacter pylori transmission in the stomach promotes a prolonged and lasting inflammation by activating mediators adjusting the movement of neutrophils, macrophages, and other leukocytes, which in turn cause pathologic lesions of the gastric mucosa [ 13 , 27 ]. Histopathological diagnosis is a gold standard that specifies the degree of gastritis severity according to the USS.…”
Section: Discussionmentioning
confidence: 99%
“…Peneliti telah mengkarakterisasi kandungan gizi yang tinggi pada ikan gabus, meliputi kandungan protein, albumin, asam amino, asam lemak, vitamin, dan mineral. Semua nutrisi tersebut sangat bermanfaat dalam pencegahan dan pengobatan beberapa penyakit termasuk yang disebabkan oleh virus (Yulizal et al, 2020).…”
Section: Hasil Dan Pembahasanunclassified